As regards the question of studying operation conditions and introduction of some samples of cables in gas turbine plants of JSC «Motor Sich» - Снигирев, Владимир Максимович; Афанасьев, Алексей Иванович; Дудник, Константин Валентинович; Куклин, Алексей Владимирович (Eastern-European Journal of Enterprise Technologies, 2014)
The study of temperature conditions of thermometering cable runs of ground-based gas turbine plants in order to determine maximum temperatures during continuous operation is given in the paper. Plants include gas turbine drive (GTD), in a compartment of which it is necessary to lay cable lines, where during the rated power operation, air temperature can reach up to 100°C (with places of local overheating above 200°C). Therefore, protection of cable lines from high temperatures is an urgent task. Testing a number of cables and thermal-insulating pipes for the stated temperature by manufacturers of these products is aimed at recommending the best of them for use in gas turbine plants. Tests have shown that thermal-insulating tubes of company «SilvynHiprojacket» and «AgrotubeC-HTS», without their internal blowing do not have the necessary thermal-insulating properties since the temperature inside and outside the tested tubes differed by a maximum of 2°C. Therefore, cables Olflexclassic 110 and 180 OlflexHeat sihf, which for a long time can withstand temperatures up to 120°C, at ambient temperature in the GTD compartment from +20°C to +55°C, which is supported by the ACS are recommended for cable lines of gas turbine plants.